Methods of teaching derived words of the Kazakh language by interactive technologies - Nurbekova, Gulshat; Odanova, Sagira; Sabdenova, Bagila; Adilbekova, Lazzat; Osmanova, Zeinep (Opción, 2018)
There are many ways to learn foreign languages taught to teachers by teachers. Analyzing language laws of branch "word formation" one can say that teaching by new technologies is of great importance. Conclusions in scientific-theoretical, methodical works, requirements in education system are a basis for drawing up the concept of training by new technologies in word formation of the Kazakh language. It is the model directed to the future. Training by new technologies is an actual problem which is implemented at each lesson of educational institution, in everyday communication, in life, deeds leading to self-improvement and self-formation of future personality.